2018
DOI: 10.1093/scan/nsy012
|View full text |Cite
|
Sign up to set email alerts
|

vmPFC activation during a stressor predicts positive emotions during stress recovery

Abstract: Despite accruing evidence showing that positive emotions facilitate stress recovery, the neural basis for this effect remains unclear. To identify the underlying mechanism, we compared stress recovery for people reflecting on a stressor while in a positive emotional context with that for people in a neutral context. While blood–oxygen-level dependent data were being collected, participants (N = 43) performed a stressful anagram task, which was followed by a recovery period during which they reflected on the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 96 publications
2
29
0
Order By: Relevance
“…However, no study has examined the relationship between stressorevoked functional vmPFC changes using a seed-based approach and stressor-evoked physiological changes. vmPFC activation has also been associated with self-reported taskrelated stress and anxiety (van der Werff et al, 2013;Wager, Waugh et al, 2009;Wheelock et al, 2016;Yang et al, 2018) and higher trait-level coping (Sinha et al, 2016). A recent study found large-scale brain networks involving the vmPFC to be associated with individual differences in stress-induced emotions (Tobia et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no study has examined the relationship between stressorevoked functional vmPFC changes using a seed-based approach and stressor-evoked physiological changes. vmPFC activation has also been associated with self-reported taskrelated stress and anxiety (van der Werff et al, 2013;Wager, Waugh et al, 2009;Wheelock et al, 2016;Yang et al, 2018) and higher trait-level coping (Sinha et al, 2016). A recent study found large-scale brain networks involving the vmPFC to be associated with individual differences in stress-induced emotions (Tobia et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The ventromedial prefrontal cortex (vmPFC) is implicated in physiological control processes, particularly involving the autonomic and cardiovascular systems (Gianaros & Wager, ; Roy, Shohamy, & Wager, ; Sinha, Lacadie, Constable, & Seo, ; Tobia, Hayashi, Ballard, Gotlib, & Waugh, ; Wager, van Ast et al, ; Wager, Waugh et al, ; Winecoff et al, ; Yang et al, ). The vmPFC has also been implicated in ascribing meaning to or evaluating the personal significance of emotionally evocative contexts (e.g., threatening stimuli) and stressors (Levy & Glimcher, ; Montague & Berns, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Product measures supported the interpretation that PC was more strongly related with 'Gastric and cardiovascular' symptoms than eBAC, and robust regression provided some validation of this model. PC has been related to activity in the mPFC [24], an anatomical area that has also been shown to mediate stress response [55]. This may provide a link through which this cognitive strategy can influence stress responses occurring as a result of hangover.…”
Section: Dimensions Of the Ahs Independently Associated With Pcmentioning
confidence: 98%
“…Gains in decentering predict acute and enduring improvement in distress disorders following treatment with mindfulness-based interventions (MBIs) [17][18][19][20] as well as mindfulness enriched CBTs [21][22][23][24]. Theoretical accounts [16,25,26] and empirical findings [27,28] are beginning to reveal the neurobehavioral underpinnings of decentering and suggest MBIs lead to engagement and enduring alterations in large-scale neural networks associated with attention, executive control, and self-referential processing [29][30][31]. However, as the science of decentering continues to mature [32], more work is need to carefully elucidate how mindfulness acts on the distressed brain possibly via increases in decentering [20].…”
Section: A Neurobehavioral Account For Decentering As the Salve For Tmentioning
confidence: 99%